Предмет: Математика, автор: NeK1TG

С решением,пожалуйста

Приложения:

Ответы

Автор ответа: m11m
0
1)  √y          -   √y + √x  √y*√y -(√y+√x)(√y-√x) =
    √y - √x              √y                     √y(√y-√x)
=   y - y +x     =         x         
   √y (√y-√x)      √y (√y - √x)

2)     √x      :             x          =    √x    *   √y (√y - √x)  =
     √y - √x       √y (√y - √x)       √y - √x           x
√x * √y  =   √x * √y  =  √y  
        x            √x * √x      √x
Похожие вопросы
Предмет: История, автор: v1i2o3l4e5tt6a
Предмет: Математика, автор: веапонп